Hubungan Pendidikan Kewarganegaraan Dengan Pancasila: Wujud Implementasi Nilai Pancasila - Andika Rizky Nugraha; Dinie Anggraeni Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research aims to describe how the values of Pancasila are implemented in community life, elementary schools and students. The research method used a qualitative approach with a literature study method. The information that is used as study material comes from literary sources such as journals, article, and books. The results showed that the implementation in the society of Pancasila Village and MI Hambail Falah has been carried out well and of course can be used as an example for the society and other students. And for the college student environment (campus), the implementation of Pancasila values can be integrated with state defense attitudes such as: love for the homeland, awareness of the nation and state, belief in Pancasila as the state ideology, a sense of willingness to sacrifice, and finally having the basic ability to defend the state